Causal Association Between Tea Consumption and Kidney Function: A Mendelian Randomization Study - Yangchang Zhang; Yangchang Zhang; Yangchang Zhang; Yangchang Zhang; Yang Xiong; Shisi Shen; Jialu Yang; Jialu Yang; Jialu Yang; Wei Wang; Wei Wang; Wei Wang; et al. (Frontiers in Nutrition, 2022)
BackgroundCausal research concerning the consumption of tea and the risk of chronic kidney disease (CKD) is limited. This study identified the potential causal effects of tea intake on CKD, the estimated glomerular filtration rate (eGFR), and albuminuria.MethodsGenome-wide association studies (GWASs) from UK Biobank were able to identify single-nucleotide polymorphisms (SNPs) associated with an extra cup of tea each day. The summary statistics for the kidney function from the CKDGen consortium include 11,765 participants (12,385 cases of CKD) and 54,116 participants for the urinary albumin-to-creatinine ratio who were mostly of European descent. A two-sample Mendelian randomization (MR) analysis was performed to test the relationship between the selected SNPs and the risk of CKD.ResultsA total of 2,672 SNPs associated with tea consumption (p < 5 × 10–8) were found, 45 of which were independent and usable in CKDGen. Drinking more cups of tea per day indicates a protective effect for CKD G3-G5 [odds ratio (OR) = 0.803; p = 0.004] and increases eGFR (β = 0.019 log ml/min/1.73 m2 per cup per day; p = 2.21 × 10–5). Excluding two SNPs responsible for directional heterogeneity (Cochran Q p = 0.02), a high consumption of tea was also negatively correlated with a lower risk of albuminuria (OR = 0.758; p = 0.002).ConclusionFrom the perspective of genes, causal relationships exist between daily extra cup of tea and the reduced risk of CKD and albuminuria and increased eGFR.